2009
DOI: 10.1371/journal.pgen.1000354
|View full text |Cite|
|
Sign up to set email alerts
|

LINE Retrotransposon RNA Is an Essential Structural and Functional Epigenetic Component of a Core Neocentromeric Chromatin

Abstract: We have previously identified and characterized the phenomenon of ectopic human centromeres, known as neocentromeres. Human neocentromeres form epigenetically at euchromatic chromosomal sites and are structurally and functionally similar to normal human centromeres. Recent studies have indicated that neocentromere formation provides a major mechanism for centromere repositioning, karyotype evolution, and speciation. Using a marker chromosome mardel(10) containing a neocentromere formed at the normal chromosoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
121
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(129 citation statements)
references
References 54 publications
6
121
2
Order By: Relevance
“…This is consistent with studies of the role of transcription and RNAi in centromere activity in S. pombe (Volpe et al, 2002(Volpe et al, , 2003Chen et al, 2008); however, the role for transcription in metazoan kinetochore activity has been little studied (Saffery et al, 2003;Fukagawa et al, 2004;Wong et al, 2007;Chueh et al, 2009). Our previous studies found that alphoid tetO kinetochore inactivation by the tTS correlated with the recruitment of heterochromatin protein HP1␣ and that direct recruitment of HP1␣ as a TetR:EYFP fusion protein could also inactivate the kinetochore (Nakano et al, 2008).…”
Section: Molecular Biology Of the Cell 4200supporting
confidence: 89%
“…This is consistent with studies of the role of transcription and RNAi in centromere activity in S. pombe (Volpe et al, 2002(Volpe et al, , 2003Chen et al, 2008); however, the role for transcription in metazoan kinetochore activity has been little studied (Saffery et al, 2003;Fukagawa et al, 2004;Wong et al, 2007;Chueh et al, 2009). Our previous studies found that alphoid tetO kinetochore inactivation by the tTS correlated with the recruitment of heterochromatin protein HP1␣ and that direct recruitment of HP1␣ as a TetR:EYFP fusion protein could also inactivate the kinetochore (Nakano et al, 2008).…”
Section: Molecular Biology Of the Cell 4200supporting
confidence: 89%
“…Centromeric satellite and retroelement transcripts have been identified in a multitude of different organisms, including rice, maize, beetle, tammar wallaby, mouse, and human, and are of various sizes, from 35 to 5,000 nt in length (Topp et al 2004;BouzinbaSegard et al 2006;Lee et al 2006;Yan et al 2006;Pezer and Ugarković 2008;Carone et al 2009;Chueh et al 2009;Ferri et al 2009;Du et al 2010). CT levels, like PCT levels, can change depending on developmental stage and tissue type.…”
Section: Centromeric Transcriptionmentioning
confidence: 99%
“…The specific function of each type of CT may be dependent on their size, with observed CTs associating with CENP-A ranging from 35 to >900 nt in length (Topp et al 2004;Chueh et al 2009;Ferri et al 2009;Du et al 2010). For example, the knockdown of a specific sized long interspersed nucleotide element (LINE), which is shown to interact with CENP-A at a human neocentromere, causes a decrease in CENP-A loading (Chueh et al 2009). CenH3 in maize was shown to interact with long CentC satellite transcripts (Du et al 2010).…”
Section: Centromeric Transcriptionmentioning
confidence: 99%
See 2 more Smart Citations